1980
DOI: 10.1128/jvi.33.1.10-17.1980
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus JHM: Cell-Free Synthesis of Structural Protein p60

Abstract: Sac(-) cells infected with murine coronavirus strain JHM shut off host cell protein synthesis and synthesized polypeptides with molecular weights of 150,000, 60,000, and 23,000. The 60,000-and 23,000-molecular-weight polypeptides comigrated with virion structural proteins p60 and p23, and the 60,000-molecularweight protein was identified as p60 by tryptic peptide fingerprinting. Polyadenylate-containing RNA [poly(A) RNA] extracted from the cytoplasm of infected cells directed the synthesis of both 60,000-and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 27 publications
4
47
1
Order By: Relevance
“…They are polyadenylated, as expected of mRNAs, and Robb and Bond (1979) have shown that multiple MHV-specific RNA species spanning the size range of the subgenomic RNAs 2-7 are present on polysomes of infected cells. Furthermore, Siddell et al (1980) have recently demonstrated that polyadenylated RNA isolated from JHMV-infected cells can be translated in vitro. Using sucrose gradients they were able to partially resolve 1'7 and 19 S JHMV-specific RNA species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are polyadenylated, as expected of mRNAs, and Robb and Bond (1979) have shown that multiple MHV-specific RNA species spanning the size range of the subgenomic RNAs 2-7 are present on polysomes of infected cells. Furthermore, Siddell et al (1980) have recently demonstrated that polyadenylated RNA isolated from JHMV-infected cells can be translated in vitro. Using sucrose gradients they were able to partially resolve 1'7 and 19 S JHMV-specific RNA species.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the data obtained on coronavirus virion RNA, few data have been published on intracellular coronavirusspecific RNA. Mishra and Ryan (1973) reported that porcine kidney cells infected with transmissible gastroenteritis virus (TGEV) contained actinomycin D-resis-tent RNA species which sedimented between 18 and 28 S. Robb and Bond (1979b) have studied murine hepatitis virus (MHV)-infected cells and found that deproteinized RNA from virus-specific polysomes sedimented between 10 and 28 S. RNA in this size range was recently demonstrated to code for two MHV structural proteins (Siddell et al, 1980). Stern and Kennedy (1980a,b) have identified six virus-specific RNA species in cells infected with avian infectious bronchitis virus (IBV).…”
Section: Introductionmentioning
confidence: 99%
“…and peaks at 6 h p.i. (Siddell et al, 1980(Siddell et al, , 1981a. An increased number of free 80S ribosomes and a shift to lighter polysomes during MHV infection suggest a potential suppression at the translation initiation phase (Anderson and Kedersha, 2009;Siddell et al, 1981b).…”
Section: Coronavirus-mediated Control Of Host Translationmentioning
confidence: 98%
“…Being obligate intracellular parasites, viruses heavily depend on host cell structures and functions to complete their life cycle, and they also use the translational apparatus of the infected cell to express their proteins. In several cases, viruses have been shown to affect and/or modulate the status of the host translational machinery to achieve efficient viral protein synthesis and replication, while cellular mRNA translation is inhibited (Hilton et al, 1986;Narayanan et al, 2008a;Siddell et al, 1980Siddell et al, , 1981a. In eukaryotic cells, translation occurs in the cytoplasm and essentially involves four steps: initiation, elongation, termination, and recycling (Kapp and Lorsch, 2004).…”
mentioning
confidence: 99%
“…Both IBV and MHV contain three main structural polypeptides: the nucleocapsid, the membrane (El), and the spike or peplomer (E2) polypeptides (Cavanagh, 1981;Siddell et al, 1983). In both systems the smallest RNA codes for the nucleocapsid protein but in MHV the next smallest RNA codes for the membrane polypeptide, whereas in IBV the membrane polypeptide is coded for by the third smallest RNA (Siddell et al, 1980;Siddell, 1983;Rottier et al, 1981;Stern et al, 1982;Stem and Sefton, 1984). These differences are summarised in Fig.…”
Section: Introductionmentioning
confidence: 99%